(untitled) (Al-Qamar, 2021)
At a time when civilizational wars are on the rise, the world’s religions and their proponents are at loggerheads in the same civilizational conflict. The religion of Islam and its followers seem to be more affected by this whole situation. There are other difficulties and punishments. Every day we come to hear and see the incidents of desecration of places of worship and other holy places of the people of Islam. But a study of history reveals that when these Muslims were in power and how the Muslim caliphs and rulers ruled the world and protected the holy places of other religions, and the followers of other religions and their worship in the Islamic Empire The places were so respected and protected that even in the areas under the control of the rulers who took the name of these religions, they did not consider themselves so safe. The need is that such events and facts scattered in the pages of history in this regard. It should be made clear to the world that Islam and Ibliyan Islam are very open and wide-hearted in this regard. In view of this, this article mentions the Islamic teachings regarding the protection of non-Muslim holy places and places of worship as well as the practical steps of Seerat-e-Tayyiba, Righteous Caliphs and various other great rulers without which the world can still seek guidance. Can be provided a peaceful and serene environment.